ANALISIS KUALITAS WEBSITE MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS : Studi Kasus Website Tokome.id - Devitasari (2020)
Tokome.id is an e-commerce company that provides merchandise manufacturing services by sending a design image of the product that we want to buy or sell. The purpose of this research is to measure the quality of the website owned by Tokome.id. To determine the quality of a website, it is necessary to measure the quality based on its users using the Webqual 4.0 method which consists of 3 variables (usability, information quality, service interaction quality), and 22 question indicators. The technique that researchers used is the Importance Performance Analysis (IPA) method which provides an overview of what indicators need improvement or need to maintain their quality based on user perceptions and expectations. Based on the results of the analysis of Importance Performance Analysis (IPA), it shows that of the 22 items analyzed using the Importance Performance analysis method, they are grouped into quadrant I (8 items), quadrant II (6 items), quadrant III (5 items), and quadrant IV (3 item). Items that are considered very important and need to be improved are located in quadrant I, namely the sense of data/information security when accessing the website. These results indicate that the quality of the Tokome.id website is still lacking and has not met user expectations.